Environmental Benefits of Internet-Enabled C2C Closed-Loop Supply Chains: A Quasi-Experimental Study of Craigslist - Dhanorkar, Suvrat (Management Science, 2019)
Recently, online matching platforms (e.g., Craigslist, FreeCycle, Gumtree) have enabled consumers to directly connect with each other to buy/sell used consumer goods (electronics, furniture, packaging, etc.) that would have otherwise ended up in the waste stream. Such matching platforms can facilitate the creation of consumer-to-consumer (C2C) closed-loop supply chains (CLSCs) for used goods, which can enhance product reuse and limit reliance on recycling and disposal alternatives. Yet, the true environmental benefits of these internet-enabled C2C CLSCs remain to be ascertained. In this study, I use a quasi-experimental setup to examine how Craigslist’s entry into various U.S. geographic markets impacts a key environmental outcome: municipal solid waste (MSW). I assemble a data set from various disparate sources to test my hypothesis. I find that, on average, Craigslist’s entry into a geographic market results in a 2%–6% annual reduction in MSW per capita generated. I conduct a variety of robustness checks, falsification tests, and validation checks to provide support to my findings. Overall, this study provides deeper insights into the potential of online reuse platforms for the creation and coordination of C2C CLSCs. To my knowledge, this is the first study of closed-loop supply chains in a C2C context. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2963 . This paper was accepted by Serguei Netessine, operations management.